Evolution of Samsung group and its central office: Imperfect market and capacity-building. Issue 5 (December 2016) - Choi, Philip
Abstract The history of Samsung and its central office shows the influence of exogenous social and economic change on business-group structures and the endogenous development of capacity in a business group. This paper investigates how transaction cost operates in regard to group size and the functions retained or otherwise, centralized or decentralized, by central office. In relation to business-group development, the effectiveness of transaction cost and active capacity-building are examined and weighed. Entrepreneurs reacting to external changes have raised group capabilities and sought to maintain group integrity. The central-office activities of allocation, ratification, nurturing, and sharing are also discussed and conceptualized.